WHY THE FUTURE OF JOURNALISM IS NOT A TECHNOLOGICAL RUPTURE: ON THE IMAGINATION OF THE SOCIETAL NEEDS OF PUBLIC COMMUNICATION AND INNOVATION IN PIONEER JOURNALISM - Hepp, Andreas; Loosen, Wiebke (AoIR Selected Papers of Internet Research, 2026)
Journalism often frames its future as shaped by “technological rupture” and “innovation”. This paper challenges such narratives, arguing instead for understanding journalism’s transformation as a broader structural change—one that involves the creation of new organizational principles, supported by an imagined need for new technologies to “innovate” toward a better future. Through the concept of “pioneer journalism,” we analyze how journalists who experiment with new practices and imagine possible futures shape the transformation of the field. Based on a media-ethnography in Germany, we examine how pioneer journalists envision the societal needs for public communication and how these imaginaries inform their approaches to innovation. Our findings reveal that their imaginations are strongly rooted in democratic values, emphasizing six societal needs: creating encompassing publics, providing appropriate information, fostering exchange, correcting negative developments, promoting a sense of belonging, and supporting societal development. Paradoxically, however, their discourse on innovation often mirrors Silicon Valley’s categories, raising critical questions about whether such frameworks can adequately address the imagined needs for public communication. There is a multiple refraction of innovation imperatives: pioneer journalists simultaneously critique Silicon Valley narratives and Big Tech power while appropriating their innovation methods, creating tensions between journalistic values and innovation practices.